Low- and Mid-Latitude Ionospheric Response to the 2013 St. Patrick’s Day Geomagnetic Storm in the American Sector: Global Ionosphere Thermosphere Model Simulation - Zhu, Qingyu; Lu, Gang; Deng, Yue (Frontiers in Astronomy and Space Sciences, 2022)
In this study, the low- and mid-latitude ionospheric response to the main phase of the 2013 St Patrick’s Day geomagnetic storm in the American sector on the dayside has been investigated using the ground-based measurements and the Global Ionosphere Thermosphere Model (GITM). First, it is found that the observed ionospheric response can be well reproduced by GITM when it is driven by the electric potential and electron precipitation patterns derived from the Assimilative Mapping of Ionospheric Electrodynamics (AMIE) technique. The AMIE-driven GITM simulation also significantly improves the data-model comparison as compared with the simulation driven by the high-latitude empirical models. Second, it is found that the transport process associated with the neutral wind is largely responsible for the observed ionospheric response. Specifically, the traveling atmospheric disturbances (TADs) propagating from the opposite hemisphere play an important role in the formation of the negative storm phase at low and middle latitudes. Third, it is found that the asymmetric negative storm phases occurred at the nominal equatorial ionization anomaly (EIA) peak region in the afternoon sector are mainly attributed to the interaction of the TADs launched in different hemispheres with different phase speeds. Specifically, stronger Joule heating deposited in the northern hemisphere (NH) generates TADs with faster phase speeds than those launched in the southern hemisphere (SH). Consequently, the locations where the TADs originated from the different hemispheres interact are asymmetric about the geomagnetic equator, leading to the formation of asymmetric ionospheric negative storm phases. This study highlights the importance of accurately specifying high-latitude electrodynamic forcings in global I-T simulations and provides a new insight into the cause of the interhemispheric asymmetry phenomena during geomagnetic storms.